A case of hypoglycemia due to illegitimate sexual enhancement medication. Issue 1 (April 2015) - Kuramoto, Naoki; Yabe, Daisuke; Kurose, Takeshi; Seino, Yutaka
Highlights Hypoglycemia by illicit sexual enhancers is a serious problem requiring awareness. A case of hypoglycemia by a sexual enhancer "Nangen Zengzhangsu" is reported. A single capsule of this medication contained a very large amount of glibenclamide.